Natural occurrences and characterization of Elizabethkingia miricola infection in cultured bullfrogs (Rana catesbeiana) - Wei, Dongdong; Cheng, Yuan; Xiao, Shuangyan; Liao, Wenyu; Yu, Qing; Han, Shuyu; Huang, Shuaishuai; Shi, Jingu; Xie, Zongsheng; Li, Pengfei (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The bacterium Elizabethkingia miricola is a multispecies pathogen associated with meningitis-like disease that has been isolated from several amphibian species, including the bullfrog, but this is the first isolation in Guangxi. In the present study, the dominant bacteria were isolated from the brains of five bullfrogs with meningitis-like disease on a South China farm in Guangxi. Methods The NFEM01 isolate was identified by Gram staining; morphological observations; 16S rRNA, rpoB, and mutT-based phylogenetic tree analysis; and physiochemical characterization and was subjected to drug sensitivity and artificial infection testing. Results and discussion As a result of identification, the NFEM01 strain was found to be E. miricola. An artificial infection experiment revealed that NFEM01 infected bullfrogs and could cause symptoms of typical meningitis-like disease. As a result of the bacterial drug sensitivity test, NFEM01 is highly sensitive to mequindox, rifampicin, enrofloxacin, nitrofural, and oxytetracycline and there was strong resistance to gentamicin, florfenicol, neomycin, penicillin, amoxicillin, doxycycline, and sulfamonomethoxine. This study provides a reference to further study the pathogenesis mechanism of E. miricola-induced bullfrog meningitislike disease and its prevention and treatment.